The channel advantage : going to market with multiple sales channels to reach more customers, sell more products, make more profit - Friedman, Lawrence G.; Furey, Timothy R. (Oxford ; Boston : Butterworth Heinemann, 1999)
'The Channel Advantage' deals with one topic, and deals with it comprehensively and rigorously: how to construct a sales channel system that will yield world-class sales performance and durable competitive advantage. This book helps readers move decisively away from the notion of channel strategy as a sideline to the core business. Building a channel advantage is the core business today, and this is an essential text and reference for all serious marketing and sales professionals and students. Channel innovation is separating market winners from market losers, and not just in leading-edge technology industries. In a business world where industry players are selling practically the same products at essentially the same prices at about the same cost, the only real source of sustainable competitive advantage is the sales channel: how you sell, not what you sell. Selling becomes a question of how to connect products with customers via the best mix of sales channels: the sales force, value-added partners, distributors, retail stores, telemarketing, and the Internet. In short, how companies sell has become as important as what they sell. 'The Channel Advantage' explains how leading companies develop strategies that integrate e-commerce, telemarketing, sales forces, and distributors to achieve superior sales performance and sustainable competitive advantage. Timothy R. Furey is chairman, CEO and co-founder of Oxford Associates, a privately held consulting firm specializing in sales and market strategy, e-commerce channel integration and market research, based in Bethesda, Maryland. Oxford has achieved an annual growth of more than forty percent since its creation in 1991 and was named one of America's 500 fastest growing private companies by Inc. Magazine in 1997. Furey, a pioneer in the use of hybrid sales and marketing strategies for blue chip companies, works extensively with senior management leadership teams to develop and implement go-to-market growth strategies. His clients include IBM, American Express, Marriott, Xerox, Fidelity Investments, Bristol-Myers Squibb, and Johnson & Johnson. Under his leadership, Oxford Associates has developed leading-edge strategies, business processes and systems for deploying and integrating multi-channel sales and marketing systems. They work to align products with the right customers via an appropriate mix of the Internet, telesales, distributors, value-added partners, and traditional sales force channels. Mr. Furey is the co-author of THE CHANNEL ADVANTAGE (Butterworth-Heinemann, August 31, 1999), which is endorsed by the CEOs of America Online, Lotus Development, Ocean Spray, and Xerox. Mr. Furey also serves on the Board of Directors of Alpha Industries (Nasdaq:AHAA), a leading semiconductor manufacturer for wireless telephone applications. Previously, Mr. Furey worked with Boston Consulting Group, Strategic Planning Associates, Kaiser Associates and the Marketing Science Institute. He earned a BA in Economics, cum laude, from Harvard University and an MBA from the Harvard Business School. Lawrence G. Friedman is an internationally recognized channel strategy consultant whose clients have included companies such as Lotus, AT & T, Canon, Compaq Digital Equipment, Microsoft and Bell Atlantic. He also held executive level positions at Andersen Consulting and Huthwaite, Inc., the sales research firm that developed the SPIN Selling Model. In 1996, Friedman, with Neil Rackham and Richard Ruff, co-authored the best-seller, GETTING PARTNERING RIGHT (McGraw-Hill). He is on the review board of the Journal of Selling and Major Account Management, which published his article, Multiple Channel Sales Strategy, in the April, 1999 issue. His firm, The Sales Strategy Institute, works with clients to identify and evaluate new go-to-market opportunities and conducts in-depth channel strategy workshops and seminars. Mr. Friedman is a frequent guest speaker and lecturer on sales and channel strategy throughout the United States, Europe and Asia. Mr. Friedman earned an MA from the University of Chicago. The first rigorous and definitive guide looking at the whole field of channel strategy Shows you how to evaluate new channels Uses real life case studies illustrating cutting edge channel management.
Introduction: the competitive advantage of sales channels; Choosing the right sales channels ... -- The starting point: product-market focus; Aligning channels with how customers buy; The impact of products on channel selection; The bottom line: the economics of channel selection; ... And building them -- The 'leveraged' sales force; Business partner (indirect) channels; Telechannels; The Internet; Managing channels for high performance -- The art of channel mix and integration; Investing in (and across) a portfolio of channels; Measuring and managing channel performance.
Includes bibliographical references and index.
Print version record.
Keywords: Marketing channels; BUSINESS & ECONOMICS -- International -- Marketing; BUSINESS & ECONOMICS -- Marketing -- Multilevel; BUSINESS & ECONOMICS -- Exports & Imports; Marketing channels; Distributiekanalen; Marketing; Electronic books